Increased conditioned place preference for cocaine in high anxiety related behavior (HAB) mice is associated with an increased activation in the accumbens corridor - Prast, Janine M.; Schardl, Aurelia; Sartori, Simone B.; Singewald, Nicolas; Saria, Alois; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2014)
Anxiety disorders and substance use disorders are strongly associated in humans. Accordingly, a widely held but controversial concept in the addiction field, the so-called "self-medication hypothesis", posits that anxious individuals are more vulnerable for drug dependence because they use drugs of abuse to alleviate their anxiety. We tested this hypothesis under controlled experimental conditions by quantifying the conditioned place preference (CPP) to 15 mg/kg i.p. cocaine given contingently (COCAINE) in CD1 mice selectively bred for high anxiety-related behavior (HAB) vs normal anxiety-related behavior (NAB). Cocaine was conditioned to the initially nonpreferred compartment in an alternate day design (cocaine vs saline, 4 pairings each). HAB and NAB mice were also tested for the effects of noncontingent (NONCONT) cocaine administration. HAB mice showed a slightly higher bias for one of the conditioning compartments during the pretest than NAB mice that became statistically significant (p=0.045) only after pooling COCAINE and NONCONT groups. Cocaine CPP was higher (p=0.0035) in HAB compared to NAB mice. The increased cocaine CPP was associated with an increased expression of the immediate early genes c-Fos and Early Growth Related Protein 1 (EGR1) in the accumbens corridor, i.e., a region stretching from the anterior commissure to the interhemispheric border and comprising the medial nucleus accumbens core and shell, the major island of Calleja and intermediate part of the lateral septum, as well as the vertical limb of the diagonal band and medial septum. The cocaine CPP-induced EGR1 expression was only observed in D1- and D2-medium spiny neurons, whereas other types of neurons or glial cells were not involved. With respect to the activation by contingent vs noncontingent cocaine EGR1 seemed to be a more sensitive marker than c-Fos. Our findings suggest that cocaine may be more rewarding in high anxiety individuals, plausibly due to an anxiolytic effect.